The digital public domain : foundations for an open culture - Dulong de Rosnay, Mélanie; De Martin, Juan Carlos (Open Book Publishers, 2012)
Foreword by Charles Nesson -- Introduction by Melanie Dulong de Rosnay and Juan Carlos De Martin -- Manifesto and policy recommendations -- I. Introducing the digital public domain -- 1. Communia and the European public domain project : a politics of the public domain / Giancarlo Frosio -- II. Legal framework -- 2. Consume and share : making copyright fit for the digital agenda / Marco Ricolfi -- 3. Evaluating Directive 2001/29/EC in the light of the digital public domain / Lucie Guibault -- 4. Building digital commons through open access management of copyright-related rights / Giuseppe Mazziotti -- -- III. Developments and case studies -- 5. Contractually-constructed research commons : a critical economic appraisal / Enrico Bertacchini -- 6. Social motivations and incentives in ex situ conservation of microbial genetic resources / Tom Dedeurwaerdere, Per M. Stromberg and Unai Pascual -- 7. Open knowledge : promises and challenges / Rufus Pollock and Jo Walsh -- 8. Science commons : building the research web / Kaitlin Thaney -- 9. The DRIVER project : the socio-economic benefits of a European scientific commons / Karen Van Godtsenhoven -- 10. CC Rel : the creative commons rights expression language / Hal Abelson, Ben Adida, Mike Linksvayer and Nathan Yergler -- 11. The value of registering creative works / Rolan Alton-Scheidl, Joe Benso and Martin Springer -- Select bibliography of resources cited.
Copyright: The articles of this book are licensed under a Creative Commons Attribution 3.0 unported license. For more detailed information consult the publishers website.
Keywords: Internet -- Law and legislation.; Public domain (Copyright law) -- Europe.; Fair use (Copyright); Intellectual property.; Copyright and electronic data processing.; Public domain (Copyright law); Digital rights management.; Intellectual Property; Droit d'auteur -- Domaine public.; Gestion numérique des droits.; Droit d'auteur et informatique.; Droit d'auteur -- Domaine public -- Europe.; Propriété intellectuelle.; intellectual property.; Copyright law.; Intellectual property law.; Law.; Laws of Specific jurisdictions.; LAW -- Administrative Law & Regulatory Practice.; LAW -- Computer & Internet.; Europe.; Lizenz; Urheberrecht; Digitalisierung; Copyright; Creative commons; The Commons; Communia; Cultural studies; Open culture; Internet regulation; Licensing; Digital age; Digitization; Copyright law; Electronic books.